Analisis Determinan Impor Gula Indonesia - Mudzofar, Ahmad; Bowo, Prasetyo Ari (Efficient: Indonesian Journal of Development Economics, 2020)
Sugar is one of the basic foodstuffs that is useful as a sweetener for food or drinks. A decrease in sugar production and an increase in sugar consumption both on a household and industrial scale, has made Indonesia increasingly unable to meet domestic sugar needs. So the steps taken by the government to be able to meet domestic sugar needs is to import. This study aims to identify the factors that influenced the import of Indonesian sugar in 1981-2018. The analytical method used is Error Correction Model (ECM). The results of this study indicate that in the short and long term the variable of Indonesian sugar production in the previous year, and the shortage of Indonesian sugar have a negative and significant effect on the Indonesia's sugar imports, while the difference between the domestic sugar price and the world sugar price has a positive and significant effect on the Indonesia's sugar imports. Whereas the sugar import variable of the previous year and the rupiah exchange rate both in the short and long term had no significant effect on the Indonesia's sugar imports. The government should tighten the sugar import licensing regulations while still trying to increase domestic sugar production. Gula merupakan salah satu bahan pangan pokok yang berguna sebagai bahan pemanis baik untuk makanan ataupun minuman. Terjadinya penurunan produksi gula serta peningkatan konsumsi gula baik skala rumah tangga maupun skala industri, menyebabkan Indonesia semakin tidak mampu mencukupi kebutuhan gula domestik. Sehingga langkah yang dilakukan pemerintah untuk dapat mencukupi kebutuhan gula domestik adalah dengan melakukan impor. Penelitian ini bertujuan untuk mengidentifikasi faktor – faktor yang mempengaruhi impor gula Indonesia tahun 1981-2018. Metode analisis yang digunakan adalah Error Correction Model (ECM). Hasil penelitian ini menunjukkan bahwa dalam jangka pendek dan jangka panjang variabel produksi gula Indonesia tahun sebelumnya berpengaruh negatif dan signifikan terhadap impor gula Indonesia, sementara variabel shortage gula Indonesia dan selisih harga gula domestik dengan harga gula dunia berpengaruh positif dan signifikan terhadap impor gula Indonesia. Sedangkan variabel impor gula tahun sebelumnya dan nilai tukar rupiah baik dalam jangka pendek dan jangka panjang tidak berpengaruh signifikan terhadap impor gula Indonesia. Saran yang berkaitan dengan penelitian ini yaitu pemerintah hendaknya memperketat peraturan perizinan impor gula sembari tetap berusaha untuk meningkatkan produksi gula dalam negeri.